Hubungan Kemampuan Fitur Canva dengan Persepsi Keterbacaan Teks Slide Mahasiswa Teknologi Pendidikan A 2025 pada Mata Kuliah Media Pembelajaran - Suci Hilma Marini Kania; Haninda Aisyah Fitri; Dzikrina Khairunnisa; Nada Isya Agustin (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2026)
Effective presentation slides are a crucial element in the higher education learning process to enhance audience information retention. This study aims to investigate the relationship between students' ability to utilize design features on the Canva platform and the perceived readability of text in the resulting presentation slides. The primary issue addressed is the gap between the technical ease offered by Canva and students' understanding of the principles of visual communication and readability. This research employs a quantitative approach with a correlational method. The respondents consisted of 46 students from the Educational Technology Study Program at the Universitas Pendidikan Indonesia, Class A, Batch 2025. Data were collected via an online questionnaire using a 1-4 Likert scale and analyzed using the Spearman’s Rho correlation test via SPSS software. The results show a very strong and statistically significant relationship between the ability to use Canva features and the perception of text readability, with a correlation coefficient of 0.897 and a significance value of 0.000 (p < 0.05). These findings indicate that mastery of design elements such as typography selection, color contrast, and layout arrangement directly affects the quality of information readability. The study concludes that technical design skills are a primary supporting factor in creating communicative learning media. It is recommended that students further explore visual principles so that slides are not only aesthetic but also functional for the audience..